2021
DOI: 10.1111/1440-1630.12778
|View full text |Cite
|
Sign up to set email alerts
|

The parenting occupations and purposes conceptual framework: A scoping review of ‘doing’ parenting

Abstract: Introduction: Parenting is a valued, common and challenging adult role.Many parents, including some living with disability or difficult social circumstances, experience barriers to fulfilling their parenting roles. Yet, occupational therapy involvement in parenting is rarely documented. Current understandings about 'doing' parenting lack cohesion and are dispersed in occupational therapy literature. This study aims to map and synthesise occupational therapy literature on 'doing' parenting to describe the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
(71 reference statements)
0
11
0
3
Order By: Relevance
“…All diese Betätigungen lassen sich zehn Kategorien zuordnen, die im „Parenting Occupations and Purposes (POP) framework“ zusammengefasst sind (PARENTING OCCUPATIONS, S. 25). Die verschiedenen Betätigungen werden im Modell einem bestimmten Zweck zugeordnet: die Grundbedürfnisse sowie die entwicklungsrelevanten und die sozialen Bedürfnisse des Kindes zu erfüllen 1 . Darin enthalten sind auch Eltern-Kind-Spiele.…”
Section: Eltern Sein Ist Ständiges Tununclassified
“…All diese Betätigungen lassen sich zehn Kategorien zuordnen, die im „Parenting Occupations and Purposes (POP) framework“ zusammengefasst sind (PARENTING OCCUPATIONS, S. 25). Die verschiedenen Betätigungen werden im Modell einem bestimmten Zweck zugeordnet: die Grundbedürfnisse sowie die entwicklungsrelevanten und die sozialen Bedürfnisse des Kindes zu erfüllen 1 . Darin enthalten sind auch Eltern-Kind-Spiele.…”
Section: Eltern Sein Ist Ständiges Tununclassified
“…Parenting is a valued and complex role that is shaped by culture and context, which can be significantly impacted by a cancer diagnosis. The role of parent can be defined by the specific activities and occupations in which parents engage to meet a range of child needs (Lim et al, 2022). A cancer diagnosis can disrupt this role as there is an inherent conflict between caring for oneself and caring for others, leading to unmet supportive care needs.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for a more holistic understanding of parenting in occupational therapy across a broad range of disabilities and health conditions, including cancer (Lim et al, 2022). In a population-based study, it was found that 14-24.7% of parents with cancer have minor children (Inhestern et al, 2021), making parenting an important survivorship issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To support parents with a PD in this role, parenting assessments are essential to document their needs in all areas of care and determine the clinical interventions and resources that would be required to meet them (Michallet & Hamelin, 2016; National Council on Disability, 2012). However, barriers in occupational therapy practice are also reported, including knowledge gaps (Powell et al, 2019), few professional resources (Lampe et al, 2019; Lim et al, 2022), and a striking lack of formal assessment use with parents with a PD (Kirshbaum, 2013; Lampe et al, 2019). Consequently, little is known about how parenting assessments are designed, performed, and validated for parents with a PD.…”
Section: Introductionmentioning
confidence: 99%